Russian foreign trade Ensuring security: the role of the state and business - S. V. Kaymanakov (Путеводитель предпринимателя)
The crisis in the Russian economy are related not only to internal processes, but also caused by external factors. Identification of these adverse factors, processes, their assessment and analysis through the category of «foreign security», as well as measures to strengthen this important type of national economic security of the state and other institutions and, above all, the business is dedicated to the presentation of material.